PERBAIKAN RANCANGAN PRODUK SPRING BED DENGAN MENGGUNAKAN METODE QUALITY FUNCTION DEPLOYMENT - Lia Maretty P.; Rosnani Ginting; Ikhsan Siregar (Jurnal Teknik Industri USU, 2014)
Every company wants to earn product with optimal function but takes low production cost. Designs that more easily assembled will increase time efficiency and cause reduction in production costs. This study aimed to evaluate the product design of spring bed 6 feet by using the concept of QFD (Quality Function Deployment). Quality Function Deployment is a systematic method for identifying consumer desires and meet the requirements of the customers as one of the stages of product development from design to final product . Research with the QFD method generates the attribute most significant effect on the cost of assembly and long product assembly is the number of component which shown with the highest performance measurement is number of components. It is also supported with the highest relative weight namely number of component that used to joint the parts of spring bed. Spring bed has many constituent components , one of which is the use of nails that many so spend a lot of time in assembling a spring bed. It causes the company can not fulfil the customer demand. The number of components of the spring bed products serve as the main focus in the repairing of spring bed to reduce the assembly time so that can help company to fulfil the customer demands.